Re-enchanted : the rise of children's fantasy literature in the twentieth century - Cecire, Maria Sachiko, 1983- (University of Minnesota Press, 2019)
"Re-enchanted provides a timely analysis and alternative genealogy for children's fantasy literature, its medieval predecessors, and pop cultural afterlives. With a focus on works by authors including J.R.R. Tolkien, C.S. Lewis, Susan Cooper, Kevin Crossley Holland, J.K. Rowling, Junot Díaz, and George R.R. Martin, Maria Sachiko Cecire engages with key debates around what constitutes "high" and "low" culture in the face of current and historical crises in the humanities, political and affective uses of childhood and the mythological past, the anxieties of modernity, and the social impact of racially charged origin stories."--